2020
DOI: 10.1111/sjop.12604
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Friends and Family interview

Abstract: 2020). Factor structure of the Friends and Family interview. Scandinavian Journal of Psychology, 61, 460-469.The aim of this study was to specify the latent construct structure of the Friends and Family Interview (FFI: Steele & Steele, 2005) based on its dimensional scale coding protocol. The FFI is a semi-structured interview measuring attachment in middle childhood. We analyzed data from 341 FFI interviews with children aged 7-12 years, recruited in the Scandinavian € Oresund Region. Exploratory Factor Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The FFI shows good psychometric proprieties (56,(62)(63)(64)(65)). Cronbach's α for the reliability was 0.74 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The FFI shows good psychometric proprieties (56,(62)(63)(64)(65)). Cronbach's α for the reliability was 0.74 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Family and Friends Interview (FFI, Steele and Steele, 2005 ) is theoretically based on the AAI but was adapted to the developmental abilities of children and adolescents between 8 and 16 years. The FFI differs from the AAI by considering a child’s reality and experiences in the context of friendships, siblings, self-perception and reflective functioning dimensions ( Pace, 2014 ; Pace et al, 2020 ; Psouni et al, 2020 ). As the FFI inquiries about the adolescents’ view of the conflicting emotions arising in their close relationships rather than comparing semantic and episodic memories of past experiences with attachment figures like in the AAI ( Pace, 2014 ), this technique might cause a higher emotional intensity and thus reveal different physiological patterns in those with a resolved and an unsolved attachment status.…”
Section: Discussionmentioning
confidence: 99%
“…DOI: 10.1159/000521393 Discriminant Validity. Steele & Steele (2005) reported that older children were scored higher on narrative coherence, although other studies reported that attachment indices were not significantly related to age Groza et al, 2012;Kerns et al, 2015;Obeldobel & Kerns, 2020;Pace et al, 2015;Psouni & Apetroaia, 2014;Psouni et al, 2020). Regarding gender, Barcons et al (2012) found that girls were scored higher on security, while other studies reported nonsignificant associations between FFI attachment indices and gender Kerns et al, 2015;Obeldobel & Kerns, 2020;Pace et al, 2015;Psouni & Apetroaia, 2014;Psouni et al, 2020;Steele & Steele, 2005).…”
Section: Autobiographical Interviewsmentioning
confidence: 99%
“…Steele & Steele (2005) reported that older children were scored higher on narrative coherence, although other studies reported that attachment indices were not significantly related to age Groza et al, 2012;Kerns et al, 2015;Obeldobel & Kerns, 2020;Pace et al, 2015;Psouni & Apetroaia, 2014;Psouni et al, 2020). Regarding gender, Barcons et al (2012) found that girls were scored higher on security, while other studies reported nonsignificant associations between FFI attachment indices and gender Kerns et al, 2015;Obeldobel & Kerns, 2020;Pace et al, 2015;Psouni & Apetroaia, 2014;Psouni et al, 2020;Steele & Steele, 2005). Regarding verbal intelligence, Obeldobel and Kerns (2020) found that maternal secure base availability was associated with higher verbal intelligence and had nonsignificant associations with other attachment indices they assessed (narrative coherence, maternal safe haven availability, paternal safe haven and secure base availability), and Steele & Steele (2005) did not find significant associations with attachment indices and verbal intelligence.…”
Section: Autobiographical Interviewsmentioning
confidence: 99%